2017
DOI: 10.1371/journal.pone.0185728
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of DAA failure and the clinical impact of retreatment in real-life patients treated in the advanced stage of liver disease: Interim evaluations from the PITER network

Abstract: BackgroundFew data are available on the virological and clinical outcomes of advanced liver disease patients retreated after first-line DAA failure.AimTo evaluate DAA failure incidence and the retreatment clinical impact in patients treated in the advanced liver disease stage.MethodsData on HCV genotype, liver disease severity, and first and second line DAA regimens were prospectively collected in consecutive patients who reached the 12-week post-treatment and retreatment evaluations from January 2015 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 32 publications
6
38
1
1
Order By: Relevance
“…After successful DAA treatment, preliminary data have shown an improvement in Child-Pugh class (observed in 85% of coinfected and in 65.9% of monoinfected patients, with no significant difference between the two groups), suggesting that viral eradication helps liver function recovery in the majority of patients with liver cirrhosis (data not shown). As previously reported, HCV cured after DAA therapy induce a reduction of the risk of HCC occurrence compared with non-responders; however, a residual risk still persists even after viral eradication [23][24][25][26]. In particular, regarding the HCC occurrence following viral eradication, the cumulative incidence was 2.2% in coinfected and 3.9% in monoinfected patients, significantly lower compared to the cumulative incidence of HCC (13.8%) reported in patients who experienced treatment failure in the PITER cohort [23].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…After successful DAA treatment, preliminary data have shown an improvement in Child-Pugh class (observed in 85% of coinfected and in 65.9% of monoinfected patients, with no significant difference between the two groups), suggesting that viral eradication helps liver function recovery in the majority of patients with liver cirrhosis (data not shown). As previously reported, HCV cured after DAA therapy induce a reduction of the risk of HCC occurrence compared with non-responders; however, a residual risk still persists even after viral eradication [23][24][25][26]. In particular, regarding the HCC occurrence following viral eradication, the cumulative incidence was 2.2% in coinfected and 3.9% in monoinfected patients, significantly lower compared to the cumulative incidence of HCC (13.8%) reported in patients who experienced treatment failure in the PITER cohort [23].…”
Section: Discussionsupporting
confidence: 57%
“…As previously reported, HCV cured after DAA therapy induce a reduction of the risk of HCC occurrence compared with non-responders; however, a residual risk still persists even after viral eradication [23][24][25][26]. In particular, regarding the HCC occurrence following viral eradication, the cumulative incidence was 2.2% in coinfected and 3.9% in monoinfected patients, significantly lower compared to the cumulative incidence of HCC (13.8%) reported in patients who experienced treatment failure in the PITER cohort [23]. However, careful follow-up is important not only in patients with virological failure or with known risk factors (i.e., decompensation of liver cirrhosis prior to antiviral treatment or a "cured" HCC), but also in patients with F4 fibrosis stage/liver cirrhosis prior to viral eradication.…”
Section: Discussionsupporting
confidence: 57%
“…In fact, we identified several studies that specifically focus on elderly populations while others reported age‐specific subgroup analyses. While most of the studies reported comparable efficacy of DAAs in the elderly compared to younger patients, some raised concerns that higher rates of treatment failure may specifically affect subgroups with other negative predictive factors, including cirrhosis and HCV genotypes 3 and 4 . Moreover, some studies also reported higher rates of SAEs and treatment discontinuation in the elderly .…”
Section: Discussionmentioning
confidence: 99%
“…While most of the studies reported comparable efficacy of DAAs in the elderly compared to younger patients, some raised concerns that higher rates of treatment failure may specifically affect subgroups with other negative predictive factors, including cirrhosis 24 and HCV genotypes 3 and 4. [25][26][27] Moreover, some studies also reported higher rates of SAEs and treatment discontinuation in the elderly. 18,[28][29][30] These findings have raised concerns whether a 'treat all' strategy is justified given the lack of a comprehensive risk-benefit analysis in this particular patient population.…”
Section: F I G U R E 2 Subgroup Analysis For Non-sustained Virologic mentioning
confidence: 99%
“…Kondili et al . suggested that CTP class deterioration and impairment of hepatic function after repeated treatment failures could be improved by successful retreatment in a significant number of retreated patients …”
Section: Discussionmentioning
confidence: 99%